The Tibial Tuberosity-Trochlear Groove Distance Can either Increase or Decrease during Adolescent Growth - Per-Henrik Randsborg; Hasan Banitalebi; Asbjørn Årøen; Truls Straume-Næsheim (MDPI AG, 2024)
Increased Tibial Tuberosity-Trochlear Groove (TT-TG) distance is a risk factor for recurrent lateral patella dislocations (RLPD). Population-based cross-sectional studies on healthy subjects demonstrate that the TT-TG increases gradually during growth until skeletal maturity, but changes in the TT-TG distance during adolescence in patients with RLPD on an individual basis have not been previously investigated. This study aimed to measure changes in TT-TG distance during skeletal maturity. The TT-TG of 13 consecutive patients with open physes (mean age 13 years) with RLPD was measured on MRI at baseline and three years later. The change in TT-TG distance over the three-year period was measured. The mean change in TT-TG distance from the baseline to the three-year follow-up increased overall (2.9 mm, 95% Confidence Interval (CI) 2.1-3.7). However, the TT-TG distance could either increase or decrease during final growth. Our results suggest that the TT-TG distance in patients suffering from RLPD may either decrease or increase individually during the growth spurt. This contradicts the current concept that the TT-TG distance increases gradually during growth.